2007
DOI: 10.1002/14651858.cd002813.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy for patients with Parkinson's disease

Abstract: BackgroundDespite drug and surgical therapies for Parkinson's disease, patients develop progressive disability. It has both motor and non-motor symptomatology, and their interaction with their environment can be very complex. The role of the occupational therapist is to support the patient and help them maintain their usual level of self-care, work and leisure activities for as long as possible. When it is no longer possible to maintain their usual activities, occupational therapists support individuals in cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
0
47
0
8
Order By: Relevance
“…Dixon et al's review 209 of OT for PD identified two RCTs. Both trials claimed some positive effects of OT in PD; however, the improvements were small and their clinical or statistical significance was unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dixon et al's review 209 of OT for PD identified two RCTs. Both trials claimed some positive effects of OT in PD; however, the improvements were small and their clinical or statistical significance was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The types of interventions explored were OT, 209 MDC, 210 psychological interventions 211 and explicit self-management support. 81 The review exploring MDC for MND failed to identify any RCTs for inclusion.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Evidence for physiotherapy and occupational therapy in Parkinson's disease Cochrane reviews of PT and OT for PD found insufficient evidence of their individual effectiveness, but the trials included in the reviews were methodologically flawed with small size and short-term follow-up. [7][8][9] Despite this lack of evidence, the UK National Institute for Health and Care Excellence guidelines, although recognising these shortcomings and recommending further trials, stated that all patients should have access to both therapies.…”
Section: Physiotherapy and Occupational Therapymentioning
confidence: 99%
“…8,9 The Cochrane review of OT found insufficient evidence about effectiveness. 7 The absence of any motor effect (PDQ-39 mobility domain) or response in ADL in PD REHAB is likely to be multifactorial because of the early disease stage of most of the patients, the low dose of intervention, and the lack of consistency in therapy assessment and intervention approaches.…”
Section: Lack Of Responsementioning
confidence: 99%